2023
DOI: 10.1111/ipd.13100
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐behavioural determinants associated with the first dental visit in Saudi children: A cross‐sectional study

Ravi Kumar Gudipaneni,
Munahi Abdullah Rushdallah Alsirhani,
Musab Redha S. Alruwaili
et al.

Abstract: ObjectiveThis study aimed to determine the age at which Saudi children had their first dental visit (FDV) and the socio‐behavioural predictors associated with these visits in Al Jouf Province, Kingdom of Saudi Arabia.MethodsThis cross‐sectional study used a multistage stratified random sampling technique to invite 566 parents/guardians of schoolchildren aged 12 years or younger. Multinomial logistic regression analysis was used to identify socio‐behavioural variables that predict children's FDV. P < 0.05 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Considering the socio-demographic factors that influence the proper age for FDV, it was found that parental age was a strong predictor, as a tendency toward late FDV was detected in parents with older ages, which was supported by the previous study [ 21 ]. Children who did not have siblings tended to have FDV at earlier ages compared to children with siblings.…”
Section: Discussionsupporting
confidence: 77%
“…Considering the socio-demographic factors that influence the proper age for FDV, it was found that parental age was a strong predictor, as a tendency toward late FDV was detected in parents with older ages, which was supported by the previous study [ 21 ]. Children who did not have siblings tended to have FDV at earlier ages compared to children with siblings.…”
Section: Discussionsupporting
confidence: 77%